Let's get cynical about this! Recursive relationships between psychological contract breach and counterproductive work behaviour. Issue 2 (12th January 2018) - Griep, Yannick; Vantilborgh, Tim
Abstract : Although counterproductive work behaviour towards the organization (CWB‐O) or supervisors (CWB‐S) is commonly treated as a reaction to psychological contract breach (PCB), we propose that the PCB‐CWB relationship is recursive and that CWB may increase the likelihood to perceive PCB through its effects on self‐esteem and subsequently on organizational cynicism. By estimating a two‐level time‐lagged mediation model on daily data from 103 US employees (904 observations), we found evidence for this hypothesized chain of events. These findings demonstrate that PCB and CWB happen with reference to past perceptions of PCB and/or CWB and future anticipations of PCB and/or CWB. We discuss suggestions for future research and novel practical implications in preventing further escalation. Practitioner points: When employees perceive that their organization has breached its obligations, employees are likely to retaliate by engaging in acts of CWB‐O and CWB‐S. Employees are likely to suffer from reduced self‐esteem and increased cynicism when they have engaged in CWB‐S following a PC breach. When employees become more cynical, they are more likely to perceive future PC breaches. Based on the reciprocal nature of our findings, this study highlights the need to update existing theories, as well as indicates the need for swift interventions in the aftermath of PC breach and enactment of CWB.